The role played by supply chain strategies and supply chain integration in financial performance: An empirical study in Peru - Francisco Alejandro Pérez Gilabert; Jorge Luis Pena Acevedo (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2022)
The objective of this study is to develop and test a framework for the role that supply chain strategy (SCS) and supply chain integration have in a firm's financial performance and to increase the understanding of the role that these factors play in supply chain design. Structural equation modeling was used to test these relationships based on data obtained from small and medium exporting enterprises in Peru. This study responds to a gap in understanding the role of supply chains in small and medium enterprises (SMEs) and how firms in Latin America, especially in Peru, apply supply chain concepts. Findings indicate that companies should prioritize their integration efforts depending on the type of supply chain strategy. Likewise, results show that customer integration is directly related to a firm's financial performance. This study responds to the need to understand the development of supply chain strategies and the generation of competitive advantage in Peruvian export-manufacturing SMEs.
Keywords: C44; L00; L60; N66; 330; small and medium enterprises; structural equation modeling; supply chain strategies; supply chain integration; financial performance